2019
DOI: 10.1021/acs.jpca.9b08854
|View full text |Cite
|
Sign up to set email alerts
|

On the Rise: Experimental and Computational Vibrational Sum Frequency Spectroscopy Studies of Pyruvic Acid and Its Surface-Active Oligomer Species at the Air–Water Interface

Abstract: It is well known that atmospheric aerosol play important roles in the environment. However, there is still much to learn about the processes that form aerosols, particularly aqueous secondary organic aerosols. While pyruvic acid (PA) is often better known for its biological significance, it is also an abundant atmospheric secondary organic ketoacid. It has been shown that, in bulk aqueous environments, PA exists in equilibrium between unhydrated α-keto carboxylic acid (PYA) and singly hydrated geminal diol car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 117 publications
0
41
0
Order By: Relevance
“…However, the interfacial mechanisms remain poorly understood. Using vibrational sum-frequency spectroscopy, Gordon and co-workers identified the oligomers PPA and ZYA at the air–water interfaces of PYA solutions, demonstrating that these compounds are surface active. Additionally, they performed MD simulations in the bulk and at the air–water interface; the corresponding density profiles are collected in Figure .…”
Section: Direct Photooxidation Of Organic Speciesmentioning
confidence: 99%
“…However, the interfacial mechanisms remain poorly understood. Using vibrational sum-frequency spectroscopy, Gordon and co-workers identified the oligomers PPA and ZYA at the air–water interfaces of PYA solutions, demonstrating that these compounds are surface active. Additionally, they performed MD simulations in the bulk and at the air–water interface; the corresponding density profiles are collected in Figure .…”
Section: Direct Photooxidation Of Organic Speciesmentioning
confidence: 99%
“…Surface specific methods used to study the air-water interface include second-harmonic generation, [72][73][74] X-ray photoelectron spectroscopy, 75 sum-frequency generation (SFG), [76][77][78][79][80][81][82][83][84][85][86][87][88][89] and Infrared Reflectance Absorption Spectroscopy (IRRAS). 56,57,[90][91][92][93][94][95][96][97][98][99][100][101] Of these, IRRAS and SFG allow for vibrational characterization of molecules and also provide information about the surface morphology including orientation and packing of interfacial species.…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of SFG is the stringent surface selectivity inherent to these non-linear techniques which only observe anisotropic, non-centrosymmetric species in a medium without inversion symmetry, like the air-water interface. 79,102 Though the interpretation of vibrational SFG signals is relatively complicated, as they are comprised of both resonant and nonresonant components, 102 SFG has been successfully applied to study interfacial oxoacids, specifically PA. Gordon et al 80 measured and assigned the surface spectrum of a PA solution and identified the hydrated diol form of PA, parapyruvic acid, and zymonic acid, at the surface, the latter two of which are oligomeric species known to spontaneously form from PA in aqueous environments. The Gordon et al 80 work showcases the utility of SFG for the investigation of oxoacids and further highlights the need to understand their interfacial phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…(2002) show that pyruvic acid decarboxylates under pressure to form acetic acid and carbon dioxide and undergoes aldol condensation to form dimers and trimers; a large fraction of these decarboxylate to form methyl succinate, and some undergo Diels‐Alder cyclization. Pyruvic acid dimers are important in atmospheric chemistry because they are surface‐active (B. P. Gordon et al., 2019; Hazen et al., 2002) and cyclize in droplets (Perkins et al., 2016; S. S. Petters et al., 2020). Aldol reactions are a hypothesized route for reactive uptake of gases or modification of aerosol optical properties when catalyzed by inorganic salts (Nozière et al., 2010), and have been suggested for highly acidic particles and in evaporating droplets (De Haan et al., 2009; Herrmann et al., 2015; Jang et al., 2002).…”
Section: Implications For Multiphase Atmospheric Chemistrymentioning
confidence: 99%